Clinical trial of proton craniospinal irradiation for leptomeningeal metastases. Issue 1 (27th June 2020) - Yang, T Jonathan; Wijetunga, Neil A; Yamada, Josh; Wolden, Suzanne; Mehallow, Michelle; Goldman, Debra A; Zhang, Zhigang; Young, Robert J; Kris, Mark G; Yu, Helena A; Seidman, Andrew D; Gavrilovic, Igor T; et al.
Abstract: Background: Leptomeningeal metastases (LM) are associated with limited survival and treatment options. While involved-field radiotherapy is effective for local palliation, it lacks durability. We evaluated the toxicities of proton craniospinal irradiation (CSI), a treatment encompassing the entire central nervous system (CNS) compartment, for patients with LM from solid tumors. Methods: We enrolled patients with LM to receive hypofractionated proton CSI in this phase I prospective trial. The primary endpoint was to describe treatment-related toxicity, with dose-limiting toxicity (DLT) defined as any radiation-related grade 3 non-hematologic toxicity or grade 4 hematologic toxicity according to the Common Terminology Criteria for Adverse Events that occurred during or within 4 weeks of completion of proton CSI. Secondary endpoints included CNS progression-free survival (PFS) and overall survival (OS). Results: We enrolled 24 patients between June 2018 and April 2019. Their median follow-up was 11 months. Twenty patients were evaluable for protocol treatment–related toxicities and 21 for CNS PFS and OS. Two patients in the dose expansion cohort experienced DLTs consisted of grade 4 lymphopenia, grade 4 thrombocytopenia, and/or grade 3 fatigue. All DLTs resolved without medical intervention. The median CNS PFS was 7 months (95% CI: 5–13) and the median OS was 8 months (95% CI: 6 to not reached). Four patients (19%) were progression-free in the CNS for more than 12 months. Conclusion: Hypofractionated proton CSI using proton therapy is a safe treatment for patients with LM from solid tumors. We saw durable disease control in some patients.